RBM20-mutations induce disturbed splicing of calcium relevant genes in patient-specific stem cell models of cardiomyopathies. (25th November 2020) - Rebs, S; Sedaghat-Hamedani, F; Kayvanpour, E; Huebscher, D; Katus, H; Hasenfuss, G; Meder, B; Streckfuss-Boemeke, K
Abstract: Background and aim: Mutations in the splice factor RBM20 have been identified to account for ∼3% of cardiomyopathies. In particular, the highly conserved RS-domain is a hotspot for disease-associated mutations. Distinct mutations at position 634 in the RS-domain were already described to be associated to dilative cardiomyopathy (DCM) (R634W) or to left ventricular non-compaction cardiomyopathy (LVNC) (R634L), but the molecular mechanisms that govern the heterogenic entity of DCM and LVNC remain largely unknown. We aimed to analyze the molecular driver behind the RBM20 mutation-based DCM and LVNC in a patient-specific stem cell model. Methods: Human somatic cells from 2 DCM- and 2 LVNC-patients harboring the RBM20-mutations R634W (DCM) or R634L (LVNC) were reprogrammed into induced pluripotent stem cells (iPSC) and differentiated into functional cardiomyocytes (CM). Gene expression, alternative splicing activity, sarcomeric regularity, cAMP level, kinase-specific phosphorylation of important Ca2+ players, and physiological cardiac functions as Ca2+ homeostasis were analyzed (Fluo3 and Fura4). Isogenic rescue lines were generated by CRISPR/Cas9 technology to analyze the direct impact of the RBM20 mutations to the cardiac phenotype. Results: We investigated the role of RBM20 mutations in DCM and LVNC-iPSC-CMs RBM20-splicing and observed common splice defects in titin-isoform-switch or a 24bp insertion in the gene ryanodine receptor 2 (RYR2).. In contrast, the calcium-handling gene Camk2δ was predominantly mis-spliced in LVNC-CMs, whereas the structural gene LDB3 was mis-spliced in DCM-CMs. As a possible consequence of splice defects in sarcomeric genes both DCM and LVNC-CMs exhibited an irregular sarcomeric structure at the Z-disk and M-line. Interestingly, the LVNC-CMs showed faster Ca2+ transient decay time and weakened response to β-adrenergic stimulation. In contrast, the DCM-CMs did exhibit increased Ca2+-sparks and decreased systolic and diastolic Ca2+ highlighting that two distinct missense mutations can lead to different pathological Ca2+ phenotypes. Ca2+ kinetic defects in LVNC-iPSC-CMs were independent of cAMP, but in line with Camk2δ-dependent hyperphosphorylation of the specific target PLN. Isogenic WT-iPSC lines were generated using CRISPR/Cas9 technology and underscored the role of RBM20-mutations in cardiomyopathies as the sarcomeric defects, Ca2+ cycling and leakage were rescued for both LVNC-CMs and DCM-CMs. Conclusion: We show the first iPSC-model of splice-defect-associated RBM20-dependent LVNC and DCM. Our data demonstrate that RBM20-R634L induce mis-splicing of Camk2δ leading to hyperphosphorylation of PLN-Thr17 along with increased Ca2+ kinetics in LVNC, whereas RBM20-R634W induced RYR2-dependent Ca2+ leak with disturbed systolic and diastolic Ca2+in DCM. Taken together these results suggest that the molecular aberrations in alternative splicing differ depending on the distinct missense mutation in RBM20. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): BMBF, DZHK German Center for Cardiovascular research